ANALISIS KETERAMPILAN GRAFIK SISWA SMA - Tismi Dipalaya; St. Muriati St. Muriati; Feri Firmansyah; Angelin Wardiarini (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The 21st Century educational paradigm requires students to have various life skills in dealing with the information and digital era. Scientific literacy and quantitative skills are important for students to have as life skills. Scientific literacy helps students develop cognitive reasoning and scientific attitudes. This competency assists students in processing information, building arguments, and formulating solutions regarding natural processes around them. Most of the latest information from all aspects of life is presented in quantitative form. Therefore it is necessary for students to have quantitative skills in responding to challenges in the 21st century that will work a lot with quantitative data. Graphing skill is an intersection of scientific literacy and quantitative skills. Through graphing skills students have competency in understanding, criticizing, and constructing graphs. Understanding scientific information from graphs is the first step for students to solve scientific problems and transfer scientific information. Low Graphing skills become a hindering factor for students in learning scientific concepts. Therefore, this study was proposed with the aim of examining the graphing skill profile of students which includes the ability to understand, criticize, and construct graphs. This research is expected to present initial data that can be used as a reference in developing a learning activity that can develop students' graphing skills. This research is a descriptive quantitative research. The population of this study were all students of 10th grade from 23 public high schools in Makassar City. To determine the schools to be sampled, simple random sampling technique was used. Respondents for each school in this study were determined as much as 10% of the number of 10th grade students who were randomly selected. Data collection was carried out using a Graphing Inventory which was modified into Indonesian which was then tested for validity and reliability. Data analysis was performed using quantitative descriptive analysis.